The association between demographic and behavioral characteristics and sunburn among U.S. adults — National Health Interview Survey, 2010() - Holman, Dawn M. (Prev Med, 2014)
OBJECTIVE: To examine the association between demographic and behavioral characteristics and sunburn among U.S. adults. METHOD: We used 2010 National Health Interview Survey data (N = 24,970) to conduct multivariable logistic regressions examining associations with having 1 or more sunburns in the past year and having 4 or more sunburns in the past year. RESULTS: Overall, 37.1% of adults experienced sunburn in the past year. The adjusted prevalence of sunburn was particularly common among adults aged 18–29 years (52.0%), those who repeatedly burn or freckle after 2 weeks in the sun (45.9%), whites (44.3%), indoor tanners (44.1%), those with a family history of melanoma (43.9%), and those who are US-born (39.5%). Physical activity, alcohol consumption, and overweight/obesity were positively associated with sunburn (all P < 0.001); sun protection behaviors were not significantly associated with sunburn (P = 0.35). Among those who were sunburned in the past year, 12.1% experienced 4 or more sunburns. CONCLUSION: Sunburn is common, particularly among younger adults, those with a more sun-sensitive skin type, whites, those with a family history of melanoma, the highly physically active, and indoor tanners. Efforts are needed to facilitate sun-safety during outdoor recreation, improve the consistency of sun protection practices, and prevent sunburn, particularly among these subgroups.